Understanding Victims of Interpersonal Violence: A Guide for Investigators and Prosecutors - Valliere, Veronique N. (Routledge, 2020)
i Understanding Victims of Interpersonal Violence: A Guide for Investigators and Prosecutors provides accessible information for criminal justice personnel “in the trenches” with victims of violence to aid in understanding and explaining their behavior. This guide sheds light on interpersonal violence victims’ decisions and actions by providing context and naming factors that commonly impact victim responses. These include internal factors such as culture, religion, shame, and personality, as well as external factors like access to services, support systems, and resources. These factors inhibit or facilitate responses like disclosure, resistance, and participation (or lack thereof) in the prosecution of the offenders. This book also explores the influence of the perpetrator, as well as more deeply examining victim responses that typically offer challenges to investigators and prosecutors; for example, continued contact with the offender, lack of resistance, and issues in disclosure. Finally, the guide provides concrete tools to assist investigators in interviewing and for prosecutors to use during the prosecutorial process. This book is designed for investigators, prosecutors, advocates, criminal justice practitioners, and students of these subjects.